Polyterephthalic acid-2, 5-furandicarboxylic acid glycol copolyester foam material as well as preparation method and application thereof

By using modified SiO2-enhanced polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material, the existing light reflective plate preparation methods are solved, and the effects of low cost, lightweight and high reflectivity are achieved. The material is bio-based and meets the requirements of sustainable development.

CN119912791AActive Publication Date: 2025-05-02NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311437394.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

The existing light reflector plate preparation methods are costly, high in density and rely on petroleum resources, making it difficult to achieve the requirements of low cost, lightweight and high reflectivity.

Method used

Polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material is used to modify SiO2 as a bubble heterophase nucleating agent to enhance the melt strength, form a uniform small bubble cell structure, reduce density and increase light reflectivity.

Benefits of technology

Low-cost, lightweight and high reflectivity light reflective plates are achieved, and the material source is bio-based, meeting the requirements of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004528267360000161
    Figure BDA0004528267360000161
  • Figure BDA0004528267360000171
    Figure BDA0004528267360000171
  • Figure HDA0004528267610000011
    Figure HDA0004528267610000011
Patent Text Reader

Abstract

The invention relates to a polyethylene terephthalic acid-2, 5-furandicarboxylic acid glycol copolyester foam material, which is prepared from the following raw materials in percentage by mass: 90 to 99.5 percent of polyethylene terephthalic acid-2, 5-furandicarboxylic acid glycol copolyester and 0.5 to 10 percent of modified SiO2, in the polyethylene terephthalic acid-2, 5-furandicarboxylic acid glycol copolyester, a copolymerization unit is 2, 5-furandicarboxylic acid glycol copolyester, and the copolymerization unit is 2, 5-furandicarboxylic acid glycol copolyester. The molar fraction of the polyterephthalic acid-2, 5-furandicarboxylic acid is 5%-30%, the modified SiO2 comprises polysiloxane modified SiO2 and / or silane coupling agent modified SiO2, the average cell size of the polyterephthalic acid-2, 5-furandicarboxylic acid glycol copolyester foam material is smaller than or equal to 22 mm, the density is smaller than or equal to 0.37 g / cm < 3 >, and the light reflectivity is larger than or equal to 90%. The invention also provides a preparation method and application of the polyethylene terephthalic acid-2, 5-furandicarboxylic acid glycol copolyester foam material, and a light reflecting plate prepared from the polyethylene terephthalic acid-2, 5-furandicarboxylic acid glycol copolyester foam material meets the requirements of low cost, light weight and high reflectivity, and has a bio-based source.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foaming materials, in particular to a polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material and a preparation method and application thereof. Background Art

[0002] Light reflective plates based on polyethylene terephthalate (PET) are widely used in the backlight modules of LCD TVs, mobile phones, tablet computers, and LED lighting, and are generally prepared by coating or biaxial stretching. However, on the one hand, the current preparation method is costly, and the density of the prepared light reflective plates is high (usually around 0.8 g / cm 3 On the other hand, PET is a petroleum-based polymer and is heavily dependent on petroleum resources.

[0003] As a bio-based material, polyethylene 2,5-furandicarboxylate (PEF) has a similar structure to petroleum-based PET and has excellent gas barrier, mechanical, thermal properties, etc., especially environmental friendliness. The development of PEF is of great significance for achieving sustainable development of the polyester industry. However, due to the high cost of PEF synthesis at present, the development of polyethylene terephthalate (PEFT), a new partially bio-based copolyester, will help promote the green and sustainable development of polyester materials. Therefore, the promotion of PEFT is more realistic and feasible at present. In the current era of energy conservation, emission reduction, and green environmental protection, it is of great significance to prepare low-cost, lightweight, and high-reflectivity light reflective panels. Summary of the invention

[0004] Based on this, it is necessary to provide a polyethylene terephthalate-2,5-furandicarboxylate copolyester foam material and its preparation method and application to address the above problems. The light reflection plate prepared using the polyethylene terephthalate-2,5-furandicarboxylate copolyester foam material meets the requirements of low cost, light weight and high reflectivity, and has a bio-based source.

[0005] A polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material, wherein the raw materials for preparation include 90%-99.5% of polyethylene terephthalate-2,5-furandicarboxylate copolyester and 0.5%-10% of modified SiO2, wherein the molar fraction of copolymerized 2,5-furandicarboxylic acid in the polyethylene terephthalate-2,5-furandicarboxylate copolyester is 5%-30%, the modified SiO2 includes polysiloxane-modified SiO2 and / or silane coupling agent-modified SiO2, and the polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material has an average pore size of less than or equal to 22 μm and a density of less than or equal to 0.37 g / cm 3, light reflectivity is greater than or equal to 90%.

[0006] In one embodiment, the mass fraction of the polysiloxane-modified SiO2 is 0.5%-8%;

[0007] And / or, the mass fraction of SiO2 modified by the silane coupling agent is 4%-10%.

[0008] In one embodiment, the average particle size of the polysiloxane-modified SiO2 is 20nm-85nm;

[0009] And / or, the average particle size of SiO2 modified by the silane coupling agent is 15nm-56nm.

[0010] In one embodiment, the grafting rate of the polysiloxane-modified SiO2 is 10%-35%;

[0011] And / or, the grafting rate of SiO2 modified by the silane coupling agent is 10%-55%.

[0012] In one embodiment, the polysiloxane is selected from at least one of polydimethylsiloxane, hydroxypolysiloxane or polyphenylmethylsiloxane;

[0013] And / or, the silane coupling agent is selected from at least one of hexamethyldisilazane, dodecyltrimethoxysilane or octadecyltrimethoxysilane.

[0014] In one embodiment, in the polyethylene terephthalate-2,5-furandicarboxylate copolyester, the molar fraction of the copolymerized unit 2,5-furandicarboxylic acid is 5%-15%.

[0015] A method for preparing the polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material as described above comprises the following steps:

[0016] The polyethylene terephthalate-2,5-furandicarboxylate copolyester and modified SiO2 are melt-blended and made into a sheet;

[0017] placing the sheet in a high pressure reactor for saturation to obtain a saturated sample;

[0018] The saturated sample is foamed to obtain a polyethylene terephthalate-2,5-furandicarboxylate copolyester foamed material.

[0019] In one embodiment, in the saturation step, the saturation temperature is 19° C.-23° C., the saturation pressure is 3 MPa-6 MPa, and the saturation time is 48 h-72 h.

[0020] In one embodiment, in the foaming step, the foaming temperature is 80° C.-190° C., and the foaming time is 15 s-30 s.

[0021] An application of the polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material as described above in the preparation of a light reflecting plate.

[0022] The present invention adopts polysiloxane and silane coupling agent to modify the surface of SiO2 respectively, and uses the modified SiO2 as a bubble heterogeneous nucleating agent of PEFT, which can enhance the melt strength of PEFT, so that PEFT can quickly form a large number of uniform bubble nuclei during the foaming process, thereby increasing the number of bubbles and reducing the size of the bubbles. At the same time, by controlling the content of copolymerized 2,5-furandicarboxylic acid (FDCA), the rigidity of PEFT is small, a large amount of foaming gas can be adsorbed, and the upper limit of the foaming temperature is increased, thereby forming an average bubble size of less than or equal to 22 μm and a bubble density of greater than or equal to 10 8 cell / cm 3 The fine and uniform microporous structure makes the density of the finally prepared polyethylene terephthalate-2,5-furandicarboxylate copolyester foam material less than or equal to 0.37g / cm 3 , light reflectivity is greater than or equal to 90%.

[0023] In addition, enhancing the melt strength of PEFT can also broaden the foaming temperature window of PEFT, so that PEFT can be foamed in a wider temperature range, optimizing the preparation conditions. Furthermore, the polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material is applied to a light reflector, which can meet the requirements of low cost, light weight and high reflectivity, and has a bio-based source. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a cell morphology diagram of the polyethylene terephthalate-2,5-furandicarboxylate copolyester foam material of Example 1;

[0025] Figure 2 This is a cell morphology diagram of the polyethylene terephthalate-2,5-furandicarboxylate copolyester foam material of Example 4;

[0026] Figure 3 This is a cell morphology diagram of the polyethylene terephthalate-2,5-furandicarboxylate copolyester foam material of Example 6;

[0027] Figure 4 This is a cell morphology diagram of the polyethylene terephthalate-2,5-furandicarboxylate copolyester foam material of Example 9;

[0028] Figure 5This is a cell morphology diagram of the polyethylene terephthalate-2,5-furandicarboxylate copolyester foam material of Example 10;

[0029] Figure 6 This is a cell morphology diagram of the polyethylene terephthalate-2,5-furandicarboxylate copolyester foam material of Comparative Example 1;

[0030] Figure 7 This is a pore morphology diagram of the polyethylene terephthalate-2,5-furandicarboxylate copolyester foam material of comparative example 2. DETAILED DESCRIPTION

[0031] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0033] The invention provides a polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material. The preparation raw materials include 90%-99.5% of polyethylene terephthalate-2,5-furandicarboxylate copolyester and 0.5%-10% of modified SiO2, wherein the molar fraction of copolymerized 2,5-furandicarboxylic acid units in the polyethylene terephthalate-2,5-furandicarboxylate copolyester is 5%-30%, the modified SiO2 includes polysiloxane-modified SiO2 and / or silane coupling agent-modified SiO2, and the polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material has an average pore size of less than or equal to 22 μm and a density of less than or equal to 0.37 g / cm 3 , light reflectivity is greater than or equal to 90%.

[0034] The present invention adopts polysiloxane and silane coupling agent to modify the surface of SiO2 respectively, and uses the modified SiO2 as a bubble heterogeneous nucleating agent of PEFT, which can enhance the melt strength of PEFT, so that PEFT can quickly form a large number of uniform bubble nuclei during the foaming process, thereby increasing the number of bubbles and reducing the size of the bubbles. At the same time, by controlling the content of copolymerized 2,5-furandicarboxylic acid (FDCA), the rigidity of PEFT is small, a large amount of foaming gas can be adsorbed, and the upper limit of the foaming temperature is increased, thereby forming a foam with an average bubble size of less than or equal to 22 μm and a density of greater than or equal to 10 8 cell / cm 3 The fine and uniform microporous structure makes the density of the finally prepared polyethylene terephthalate-2,5-furandicarboxylate copolyester foam material less than or equal to 0.37g / cm 3 , light reflectivity is greater than or equal to 90%.

[0035] In addition, the enhanced PEFT melt strength can also broaden the PEFT foaming temperature window, thereby enabling PEFT to foam in a wider temperature range, thereby optimizing the preparation conditions. Furthermore, the polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material is applied to a light reflector, which can meet the requirements of low cost, light weight and high reflectivity, and has a bio-based source.

[0036] Optionally, the mass fraction of the polysiloxane-modified SiO2 is 0.5%-8%, and / or the mass fraction of the silane coupling agent-modified SiO2 is 4%-10%. Further preferably, the mass fraction of the polysiloxane-modified SiO2 is 0.5%-7%, and / or the mass fraction of the silane coupling agent-modified SiO2 is 4%-8%, thereby being more conducive to enhancing the melt strength of PEFT, further forming more uniform and dense bubble nuclei during the foaming process, and improving the pore structure of the polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material.

[0037] In one embodiment, when only polysiloxane-modified SiO2 is added to PEFT, and the mass fraction of the polysiloxane-modified SiO2 is 0.5%-7%, the PEFT has a foaming temperature window of 85°C-185°C and a good pore structure, a foaming ratio of 6-12 times, a pore diameter of 3μm-20μm, and a density as low as 0.11g / cm 3 The light reflectivity can reach over 90%.

[0038] In one embodiment, only SiO2 modified by silane coupling agent is added to PEFT, and the mass fraction of SiO2 modified by silane coupling agent is 4%-8%, so that PEFT has a foaming temperature window of 90°C-195°C and good foaming ability, a foaming ratio of 9-11 times, a pore diameter of 10μm-18μm, and a density as low as 0.12g / cm 3 The light reflectivity can reach over 91%.

[0039] In one embodiment, polysiloxane-modified SiO2 and silane coupling agent-modified SiO2 are added to PEFT at the same time. The polysiloxane-modified SiO2 and the silane coupling agent-modified SiO2 can be compounded in any proportion. Preferably, the mass fractions of the polysiloxane-modified SiO2 and the silane coupling agent-modified SiO2 are 3%-5% and 0.5%-1%, respectively, so that PEFT has a foaming temperature window of 90°C-210°C and a good pore structure, a foaming ratio of 7-10 times, a pore diameter of 5μm-7μm, and a density as low as 0.15g / cm 3 The light reflectivity can reach over 95%.

[0040] Optionally, the average particle size of unmodified SiO2 is 10nm-40nm, so that the SiO2 has a larger specific surface area and contains a large number of active silanol groups, which is conducive to the modification of SiO2 by polysiloxane or silane coupling agent, thereby obtaining a higher grafting rate. Further preferably, the average particle size of unmodified SiO2 is 10nm-20nm, which is more conducive to improving the grafting rate.

[0041] Optionally, the grafting rate of the polysiloxane-modified SiO2 is 10%-35%, and the grafting rate of the silane coupling agent-modified SiO2 is 10%-55%. Further preferably, the grafting rate of the polysiloxane-modified SiO2 is 10%-25%, and the grafting rate of the silane coupling agent-modified SiO2 is 20%-45%, thereby greatly improving the dispersion of SiO2 in the PEFT matrix, achieving obvious heterogeneous nucleation effect of the bubbles, reducing the bubble size, and improving the light reflectivity.

[0042] Optionally, the average particle size of the polysiloxane-modified SiO2 is 20nm-85nm; the average particle size of the silane coupling agent-modified SiO2 is 15nm-56nm. Further preferably, the average particle size of the polysiloxane-modified SiO2 is 20nm-65nm, and the average particle size of the silane coupling agent-modified SiO2 is 15nm-50nm, so that the modified SiO2 has a larger particle size than the unmodified SiO2. The use of modified SiO2 is conducive to improving the dispersion of nanoparticles in PEFT, and is conducive to improving the melt strength of PEFT, and is conducive to preparing a PEFT foaming material with a smaller cell size and a higher light reflectivity.

[0043] Optionally, the polysiloxane is preferably at least one of polydimethylsiloxane, hydroxypolysiloxane or polyphenylmethylsiloxane.

[0044] Optionally, the silane coupling agent is preferably at least one of hexamethyldisilazane, dodecyltrimethoxysilane or octadecyltrimethoxysilane.

[0045] Optionally, in the polyethylene terephthalate-2,5-furandicarboxylate copolyester, the molar fraction of the copolymerized unit 2,5-furandicarboxylic acid (FDCA) is preferably 5%-15%. Thus, the polyethylene terephthalate-2,5-furandicarboxylate copolyester with a lower FDCA content has lower rigidity, which is beneficial to the adsorption of the foaming gas, further improving the upper limit of the foaming temperature, and the prepared foaming material has smaller pore size and higher light reflectivity.

[0046] The present invention also provides a method for preparing the polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material, comprising the following steps:

[0047] S1, melt-blending polyethylene terephthalate-2,5-furandicarboxylate copolyester and modified SiO2 to form a sheet;

[0048] S2, placing the sheet in a high pressure reactor for saturation to obtain a saturated sample;

[0049] S3, foaming the saturated sample to obtain a polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material.

[0050] In step S1, the preparation method of modified SiO2 comprises the following steps:

[0051] S11, preparing SiO2 suspension;

[0052] S12, adding polysiloxane or silane coupling agent to SiO2 suspension and reacting for 6h-24h;

[0053] S13, after the reaction is completed, washing and centrifugation are performed to obtain a precipitate, and the precipitate is dried at 50° C.-90° C. to obtain modified SiO2.

[0054] In step S11, SiO2 is preferably SiO2 prepared by a gas phase method.

[0055] Before preparing the SiO2 suspension, the SiO2 is vacuum dried at 80°C-100°C for more than 12 hours to remove moisture from the SiO2.

[0056] Taking into account the effects of reaction temperature and reaction time on the grafting rate, in step S12, when polysiloxane is used to modify SiO2, the reaction conditions are: placing the SiO2 suspension at 70°C-90°C, using a weak acid to adjust the pH value of the SiO2 suspension to 3-5, or using a weak base to adjust the pH value of the SiO2 suspension to 9-11, or without pH adjustment, adding the catalyst and polysiloxane to the SiO2 suspension, and condensing and refluxing for 12h-24h; when a silane coupling agent is used to modify SiO2, the reaction conditions are: placing the SiO2 suspension at 60°C-80°C, adding a weak acid to adjust the pH value to 4-5, then adding the silane coupling agent, and condensing and refluxing for 6h-12h.

[0057] Preferably, the mass ratio of the SiO2 to the polysiloxane is 100:30-100:50.

[0058] Preferably, the mass ratio of the SiO2 to the silane coupling agent is 100:40-100:110.

[0059] Preferably, the catalyst is selected from dibutyltin dilaurate.

[0060] In step S1, polyethylene terephthalate-2,5-furandicarboxylate copolyester and the above-mentioned modified SiO2 are weighed according to mass fraction as preparation raw materials and melt-blended. The method of melt-blending is not specifically limited, and preferably, a mixture is obtained by melt-blending in an internal mixer.

[0061] Optionally, after obtaining the mixture, the mixture can be made into a powder sample by a pulverizer, and then the powder sample is made into a sheet. The method of preparing the sheet is not specifically limited, and preferably the powder sample is made into a sheet by a flat plate vulcanizer.

[0062] Optionally, in the step of using an internal mixer for melt blending, the parameters of the internal mixer are preferably: front plate temperature 245°C-255°C, middle plate temperature 250°C-260°C, rear plate temperature 250°C-260°C, and rotor speed 50rpm / min-60rpm / min.

[0063] Optionally, the thickness of the manufactured sheet is preferably 0.5 mm-2.0 mm.

[0064] In step S2, in the saturation step, the mixture is placed in a high-pressure reactor, filled with foaming gas, and after the air in the reactor is removed, saturation is performed to obtain a saturated sample.

[0065] Optionally, the foaming gas is preferably carbon dioxide.

[0066] Optionally, the saturation temperature is preferably 19°C-23°C, the saturation pressure is preferably 3MPa-6MPa, and the saturation time is preferably 48h-72h.

[0067] In step S3, after saturation is completed, the sample is quickly transferred to an oil bath at 80°C-190°C for foaming for 15s-30s to obtain a foamed sample. After foaming is completed, the foamed sample can also be quickly transferred to ice water for quenching to fix the morphology of the pores.

[0068] Optionally, the oil bath is preferably a glycerin bath or a silicone oil bath.

[0069] The present invention also provides an application of the polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material in preparing a light reflecting plate, wherein the light reflectivity of the light reflecting plate is greater than or equal to 90%.

[0070] Hereinafter, the polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material and its preparation method and application will be further described through the following specific examples.

[0071] Example 1

[0072] 20 g of hydrophilic nano-SiO2 with a particle size of 12 nm was dissolved in 400 mL of n-heptane solution in a three-necked flask and mechanically stirred. Ammonia water was added to adjust the pH value of the solution to 9. The solution was then transferred to an oil bath at 70°C, nitrogen was introduced, 0.048 g of dibutyltin dilaurate and 6 g of polydimethylsiloxane were added dropwise, and the reaction was condensed and refluxed for 24 hours under a constant temperature magnetic stirrer.

[0073] After the reaction is completed, the modified SiO2 powder is finally obtained by repeated centrifugation, washing, drying and grinding with anhydrous ethanol. The average particle size of SiO2 modified with polydimethylsiloxane is 20nm, and the grafting rate is 16.1%.

[0074] 0.75g of modified SiO2 powder and 149.25g of polyethylene terephthalate-2,5-furandicarboxylate copolyester (FDCA molar fraction of 10%) were melt blended in an internal mixer, and then sheeted using a flat vulcanizer to form a circular sheet, wherein the mass fraction of modified SiO2 was 0.5%.

[0075] The circular sheet was then placed in a high-pressure reactor at 20°C, and carbon dioxide was introduced to reach 4 MPa. After saturation for 72 hours, the pressure was quickly released, and the saturated sample was then transferred to a dimethyl silicone oil bath at 120°C for foaming for 20 seconds to obtain a foamed sample.

[0076] Example 2

[0077] 20 g of hydrophilic nano-SiO2 with a particle size of 12 nm was dissolved in 400 mL of n-heptane solution in a three-necked flask and mechanically stirred. The mixture was then transferred to an oil bath at 90°C, nitrogen was introduced, 0.048 g of dibutyltin dilaurate and 10 g of hydroxypolysiloxane were added dropwise, and the mixture was condensed and refluxed for 24 h under a constant temperature magnetic stirrer.

[0078] After the reaction is completed, the modified SiO2 powder is finally obtained by repeated centrifugation, washing, drying and grinding with anhydrous ethanol. The average particle size of the SiO2 modified by hydroxy polysiloxane is 21nm, and the grafting rate is 32.2%.

[0079] 0.75g of modified SiO2 powder and 149.25g of polyethylene terephthalate-2,5-furandicarboxylate copolyester (FDCA molar fraction of 10%) were melt blended in an internal mixer, and then sheeted using a flat vulcanizer to form a circular sheet, wherein the mass fraction of modified SiO2 was 0.5%.

[0080] The circular sheet was then placed in a high-pressure reactor at 20°C, and carbon dioxide was introduced to reach 6 MPa. After saturation for 48 hours, the pressure was quickly released, and the saturated sample was then transferred to a dimethyl silicone oil bath at 120°C for foaming for 15 seconds to obtain a foamed sample.

[0081] Example 3

[0082] 20 g of hydrophilic nano-SiO2 with a particle size of 12 nm was dissolved in 400 mL of n-heptane solution in a three-necked flask and mechanically stirred. Ammonia water was added to adjust the pH value of the solution to 11. The solution was then transferred to an oil bath at 70°C, nitrogen was introduced, 0.048 g of dibutyltin dilaurate and 8 g of polyphenylmethylsiloxane were added dropwise, and the reaction was condensed and refluxed for 12 h under a constant temperature magnetic stirrer.

[0083] After the reaction is completed, the modified SiO2 powder is finally obtained by repeated centrifugation, washing, drying and grinding with anhydrous ethanol. The average particle size of the SiO2 modified with polyphenylmethylsiloxane is 25nm, and the grafting rate is 12.7%.

[0084] 7.5g of modified SiO2 powder and 142.5g of poly(terephthalic acid-2,5-furandicarboxylic acid) copolyester (FDCA mole fraction of 10%) were melt blended in an internal mixer, and then tabletted using a flat vulcanizer to form a circular sheet, wherein the mass fraction of modified SiO2 was 5%.

[0085] The circular sheet was then placed in a high-pressure reactor at 20°C, and carbon dioxide was introduced to reach 5MPa. After saturation for 60 hours, the pressure was quickly released, and the saturated sample was then transferred to a dimethyl silicone oil bath at 150°C for foaming for 30 seconds to obtain a foamed sample.

[0086] Example 4

[0087] The difference between Example 4 and Example 1 is that 7.5 g of modified SiO2 powder and 142.5 g of polyethylene terephthalate-2,5-furandicarboxylate copolyester (FDCA molar fraction is 10%) are placed in an internal mixer for melt blending, wherein the mass fraction of modified SiO2 is 5%.

[0088] Example 5

[0089] The difference between Example 5 and Example 1 is that the molar fraction of FDCA in PEFT is 30%.

[0090] Example 6

[0091] The difference between Example 6 and Example 5 is that the mass fraction of modified SiO2 is 5%.

[0092] Example 7

[0093] The difference between Example 7 and Example 1 is that the particle size of hydrophilic nano-SiO2 is 40 nm, the average particle size of polydimethylsiloxane-modified SiO2 is 55 nm, and the grafting rate is 13.3%.

[0094] Example 8

[0095] The difference between Example 8 and Example 7 is that 7.5 g of modified SiO2 powder and 142.5 g of polyethylene terephthalate-2,5-furandicarboxylate copolyester (FDCA molar fraction is 10%) are placed in an internal mixer for melt blending, wherein the mass fraction of modified SiO2 is 5%.

[0096] Example 9

[0097] 15 g of hydrophilic nano-SiO2 with a particle size of 12 nm was dissolved in a three-necked flask with a mixed solution of 300 mL of anhydrous ethanol and water and mechanically stirred. Acetic acid was added to adjust the pH value of the solution to 4. The obtained SiO2 suspension was then transferred to an oil bath at 80°C, nitrogen was introduced, and 6 g of hexamethyldisilazane was added dropwise. Under a constant temperature magnetic stirrer, the reaction was condensed and refluxed for 6 hours.

[0098] After the reaction is completed, the modified SiO2 powder is finally obtained by repeated centrifugation, washing, drying and grinding with anhydrous ethanol. The average particle size of the SiO2 modified by hexamethyldisilazane is 15nm, and the grafting rate is 27.9%.

[0099] 7.5g of modified SiO2 powder and 142.5g of polyethylene terephthalate-2,5-furandicarboxylate copolyester (FDCA mole fraction of 10%) were melt blended in an internal mixer, and then tabletted using a flat vulcanizer to form a round sheet, wherein the mass fraction of modified SiO2 was 5%.

[0100] The circular sheet was then placed in a high-pressure reactor at 20°C, and carbon dioxide was introduced to reach 4 MPa. After saturation for 72 hours, the pressure was quickly released, and the saturated sample was then transferred to a dimethyl silicone oil bath at 120°C for foaming for 20 seconds to obtain a foamed sample.

[0101] Example 10

[0102] 10 g of hydrophilic nano-SiO2 with a particle size of 12 nm was dissolved in a three-necked flask with a mixed solution of 300 mL of anhydrous ethanol and water and mechanically stirred. Acetic acid was added to adjust the pH value of the solution to 4. The obtained SiO2 suspension was then transferred to an oil bath at 70°C, nitrogen was introduced, and 8 g of hexamethyldisilazane was added dropwise. Under a constant temperature magnetic stirrer, the reaction was condensed and refluxed for 12 hours.

[0103] After the reaction is completed, the modified SiO2 powder is finally obtained by repeated centrifugation, washing, drying and grinding with anhydrous ethanol. The average particle size of the SiO2 modified by hexamethyldisilazane is 20nm, and the grafting rate is 33.9%.

[0104] 13.5g of modified SiO2 powder and 136.5g of polyethylene terephthalate-2,5-furandicarboxylate copolyester (FDCA mole fraction of 10%) were melt blended in an internal mixer, and then tabletted using a flat vulcanizer to form a round sheet, wherein the mass fraction of modified SiO2 was 9%.

[0105] The circular sheet was then placed in a high-pressure reactor at 20°C, and carbon dioxide was introduced to reach 4 MPa. After saturation for 72 hours, the pressure was quickly released, and the saturated sample was then transferred to a dimethyl silicone oil bath at 120°C for foaming for 20 seconds to obtain a foamed sample.

[0106] Embodiment 11

[0107] 10 g of hydrophilic nano-SiO2 with a particle size of 12 nm was dissolved in a three-necked flask with a mixed solution of 200 mL of anhydrous ethanol and water and mechanically stirred. Oxalic acid was added to adjust the pH value of the solution to 4. The obtained SiO2 suspension was then transferred to an oil bath at 80°C, nitrogen was introduced, and 10 g of octadecyltrimethoxysilane was added dropwise. Under a constant temperature magnetic stirrer, the reaction was condensed and refluxed for 12 hours.

[0108] After the reaction is completed, the modified SiO2 powder is finally obtained by repeated centrifugation, washing, drying and grinding with anhydrous ethanol. The average particle size of SiO2 modified by octadecyltrimethoxysilane is 27nm, and the grafting rate is 51.5%.

[0109] 7.5g of modified SiO2 powder and 142.5g of polyethylene terephthalate-2,5-furandicarboxylate copolyester (FDCA mole fraction of 10%) were melt blended in an internal mixer, and then tabletted using a flat vulcanizer to form a round sheet, wherein the mass fraction of modified SiO2 was 5%.

[0110] The circular sheet was then placed in a high-pressure reactor at 20°C, and carbon dioxide was introduced to reach 4 MPa. After saturation for 72 hours, the pressure was quickly released, and the saturated sample was then transferred to a dimethyl silicone oil bath at 120°C for foaming for 20 seconds to obtain a foamed sample.

[0111] Example 12

[0112] 10 g of hydrophilic nano-SiO2 with a particle size of 40 nm was dissolved in a three-necked flask with a mixed solution of 200 mL of anhydrous ethanol and water and mechanically stirred. Oxalic acid was added to adjust the pH value of the solution to 4. The obtained SiO2 suspension was then transferred to an oil bath at 65°C, nitrogen was introduced, and 8 g of octadecyltrimethoxysilane was added dropwise. Under a constant temperature magnetic stirrer, the reaction was condensed and refluxed for 12 hours.

[0113] After the reaction is completed, the modified SiO2 powder is finally obtained by repeated centrifugation, washing, drying and grinding with anhydrous ethanol. The average particle size of SiO2 modified with octadecyltrimethoxysilane is 52nm, and the grafting rate is 29.6%.

[0114] 7.5g of modified SiO2 powder and 142.5g of polyethylene terephthalate-2,5-furandicarboxylate copolyester (FDCA mole fraction of 10%) were melt blended in an internal mixer, and then tabletted using a flat vulcanizer to form a round sheet, wherein the mass fraction of modified SiO2 was 5%.

[0115] The circular sheet was then placed in a high-pressure reactor at 20°C, and carbon dioxide was introduced to reach 4 MPa. After saturation for 72 hours, the pressure was quickly released, and the saturated sample was then transferred to a dimethyl silicone oil bath at 120°C for foaming for 20 seconds to obtain a foamed sample.

[0116] Example 13

[0117] 4.5 g of the modified SiO2 powder in Example 1, 1.5 g of the modified SiO2 powder in Example 9 and 144 g of polyethylene terephthalate-2,5-furandicarboxylate copolyester (FDCA molar fraction is 10%) are placed in an internal mixer for melt blending, and then pressed into sheets using a flat vulcanizer to form round sheets.

[0118] The circular sheet was then placed in a high-pressure reactor at 20°C, and carbon dioxide was introduced to reach 4 MPa. After saturation for 72 hours, the pressure was quickly released, and the saturated sample was then transferred to a dimethyl silicone oil bath at 150°C for foaming for 20 seconds to obtain a foamed sample.

[0119] Embodiment 14

[0120] 7.5 g of the modified SiO2 powder in Example 2, 1.5 g of the modified SiO2 powder in Example 10 and 141 g of polyethylene terephthalate-2,5-furandicarboxylate copolyester (FDCA molar fraction is 10%) are placed in an internal mixer for melt blending, and then pressed into sheets using a flat vulcanizer to form round sheets.

[0121] The circular sheet was then placed in a high-pressure reactor at 20°C, and carbon dioxide was introduced to reach 4 MPa. After saturation for 72 hours, the pressure was quickly released, and the saturated sample was then transferred to a dimethyl silicone oil bath at 150°C for foaming for 20 seconds to obtain a foamed sample.

[0122] Embodiment 15

[0123] 6 g of the modified SiO2 powder in Example 3, 0.75 g of the modified SiO2 powder in Example 12 and 143.25 g of polyethylene terephthalate-2,5-furandicarboxylate copolyester (FDCA molar fraction is 10%) are placed in an internal mixer for melt blending, and then pressed into sheets using a flat vulcanizer to form round sheets.

[0124] The circular sheet was then placed in a high-pressure reactor at 20°C, and carbon dioxide was introduced to reach 4 MPa. After saturation for 72 hours, the pressure was quickly released, and the saturated sample was then transferred to a dimethyl silicone oil bath at 150°C for foaming for 20 seconds to obtain a foamed sample.

[0125] Comparative Example 1

[0126] The difference between Comparative Example 1 and Example 1 is that 0.75 g of unmodified SiO2 powder and 149.25 g of polyethylene terephthalate-2,5-furandicarboxylate copolyester (FDCA mole fraction is 10%) are melt blended in an internal mixer, and then tabletted using a flat vulcanizer to form a round sheet. The mass fraction of unmodified SiO2 is 0.5%.

[0127] Comparative Example 2

[0128] The difference between Comparative Example 2 and Example 1 is that 7.5 g of unmodified SiO2 powder and 142.5 g of polyethylene terephthalate-2,5-furandicarboxylate copolyester (FDCA mole fraction is 10%) are melt blended in an internal mixer, and then tabletted using a flat vulcanizer to form a round sheet. The mass fraction of unmodified SiO2 is 5%.

[0129] Comparative Example 3

[0130] The difference between Comparative Example 3 and Example 1 is that 16.5 g of SiO2 powder modified with polydimethylsiloxane and 133.5 g of polyethylene terephthalate-2,5-furandicarboxylate copolyester (FDCA mole fraction is 10%) are melt blended in an internal mixer, and then tabletted using a flat vulcanizer to form a circular sheet. The mass fraction of the modified SiO2 is 11%.

[0131] Comparative Example 4

[0132] The difference between Comparative Example 4 and Example 9 is that 16.5 g of SiO2 powder modified by hexamethyldisilazane and 133.5 g of polyethylene terephthalate-2,5-furandicarboxylate copolyester (FDCA mole fraction is 10%) are melt blended in an internal mixer, and then tabletted by a flat vulcanizer to form a circular sheet. The mass fraction of the modified SiO2 is 11%.

[0133] Comparative Example 5

[0134] The difference between Comparative Example 5 and Example 1 and Example 9 is that 7.5g of polydimethylsiloxane-modified SiO2 powder prepared in Example 1, 9g of hexamethyldisilazane-modified SiO2 powder prepared in Example 9 and 133.5g of polyethylene terephthalate-2,5-furandicarboxylate copolyester (FDCA mole fraction is 10%) are melt blended in an internal mixer, and then tabletted using a flat vulcanizer to form a circular sheet. Among them, the mass fraction of modified SiO2 is 10%.

[0135] Table 1 shows the properties of the polyethylene terephthalate-2,5-furandicarboxylate copolyester foamed materials obtained in the above examples and comparative examples, wherein the reflectivity (95° C.) is the light reflectivity of the foamed sample tested at 95° C.

[0136] Table 1

[0137]

[0138]

[0139] Combining Table 1 and Figure 1-7 It can be seen that compared with Comparative Examples 1-5, the heterogeneous nucleation effect of the modified SiO2 in Examples 1-15 is more obvious, the pore size of the obtained foamed material is significantly reduced, all below 22 μm, the pore distribution is more uniform, and the density of the prepared PEFT foamed material is less than or equal to 0.37 g / cm 3 The upper limit of foaming temperature is increased, and the light reflectivity can reach more than 90%.

[0140] As can be seen from Table 1, Examples 1-8 selected SiO2 modified with polysiloxane, and Examples 9-12 selected SiO2 modified with silane coupling agent, wherein SiO2 modified with polysiloxane is more conducive to preparing foaming materials with small cell size, high light reflectivity and wide foaming temperature window than SiO2 modified with silane coupling agent, and is conducive to expanding the application in the field of PEFT light reflection.

[0141] It can be seen from Examples 13-15 in Table 1 that compounding polysiloxane-modified SiO2 and silane coupling agent-modified SiO2 in a suitable proportion can not only prepare small-sized bubbles similar to those of SiO2 modified with polysiloxane, but also increase the expansion ratio and reduce the material density, thereby meeting the current requirements of low cost, light weight and high reflectivity of PEFT foaming materials.

[0142] As can be seen from Table 1, the FDCA mole fraction of the PEFT of Examples 5-6 is 30%. Compared with the PEFT of Examples 1 and 4 with an FDCA mole fraction of 10%, the pore size of the obtained foamed material is increased and the light reflectivity is reduced, indicating that in PEFT, a lower FDCA mass fraction is conducive to obtaining a small pore size and a high light reflectivity.

[0143] As can be seen from Table 1, the SiO2 particle size in Examples 7-8 is 40 nm, and compared with the SiO2 with a particle size of 12 nm in Examples 1 and 4, respectively, the grafting rate of the modified SiO2 is reduced. Therefore, a smaller SiO2 particle size is beneficial to improving the grafting rate, thereby helping to improve the uniform bubble heterogeneous nucleation ability of the modified SiO2 in the PEFT matrix, enhance the melt strength of PEFT, reduce the bubble size, and increase the light reflectivity of the PEFT foaming material.

[0144] As can be seen from Table 1, in Comparative Examples 3-5, when the content of modified SiO2 is too high, it is difficult to prepare the PEFT nanocomposite material by internal mixing, and thus it is impossible to obtain the PEFT foamed sample.

[0145] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0146] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material, characterized in that: The raw materials for preparation include 90%-99.5% of polyethylene terephthalate-2,5-furandicarboxylate copolyester and 0.5%-10% of modified SiO2, wherein the molar fraction of copolymerized 2,5-furandicarboxylic acid in the polyethylene terephthalate-2,5-furandicarboxylate copolyester is 5%-30%, the modified SiO2 includes polysiloxane-modified SiO2 and / or silane coupling agent-modified SiO2, and the average pore size of the polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material is less than or equal to 22 mm, and the density is less than or equal to 0.37 g / cm 3 , light reflectivity is greater than or equal to 90%.

2. The polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material according to claim 1, characterized in that: The mass fraction of the polysiloxane-modified SiO2 is 0.5%-8%; And / or, the mass fraction of SiO2 modified by the silane coupling agent is 4%-10%.

3. The polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material according to claim 1, characterized in that: The average particle size of the polysiloxane-modified SiO2 is 20nm-85nm; And / or, the average particle size of SiO2 modified by the silane coupling agent is 15nm-56nm.

4. The polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material according to claim 1, characterized in that: The grafting rate of the polysiloxane-modified SiO2 is 10%-35%; And / or, the grafting rate of SiO2 modified by the silane coupling agent is 10%-55%.

5. The polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material according to claim 1, characterized in that: The polysiloxane is selected from at least one of polydimethylsiloxane, hydroxypolysiloxane or polyphenylmethylsiloxane; And / or, the silane coupling agent is selected from at least one of hexamethyldisilazane, dodecyltrimethoxysilane or octadecyltrimethoxysilane.

6. The polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material according to claim 1, characterized in that: In the polyethylene terephthalate-2,5-furandicarboxylate copolyester, the molar fraction of the copolymerized unit 2,5-furandicarboxylic acid is 5%-15%.

7. A method for preparing the polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The polyethylene terephthalate-2,5-furandicarboxylate copolyester and modified SiO2 are melt-blended and made into a sheet; placing the sheet in a high pressure reactor for saturation to obtain a saturated sample; The saturated sample is foamed to obtain a polyethylene terephthalate-2,5-furandicarboxylate copolyester foamed material.

8. The method for preparing the polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material according to claim 7, characterized in that: In the saturation step, the saturation temperature is 19°C-23°C, the saturation pressure is 3MPa-6MPa, and the saturation time is 48h-72h.

9. The method for preparing the polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material according to claim 7, characterized in that: In the foaming step, the foaming temperature is 85° C.-190° C., and the foaming time is 15s-30s.

10. Use of the polyethylene terephthalate-2,5-furandicarboxylate copolyester foaming material according to any one of claims 1 to 6 in the preparation of a light reflecting plate.

Citation Information

Patent Citations

  • Production method of polyether ketone and modified nano silicon dioxide foaming materials and by supercritical carbon dioxide

    CN103382260A

  • Backlight module metal back shell and preparation method thereof

    CN114428423A

  • Polyterephthalic acid-2, 5-furandicarboxylic acid glycol copolyester foam material and preparation method thereof

    CN116218015A